Digital image stabilization for vibration reduction of videos captured from Unmanned Aerial Vehicle (UAV) - Chang, Sy Luen (2013)
The purpose of this project is to study and investigate possible methods to reduce the vibration of videos captured using the unmanned aerial vehicles (UAV) using digital stabilization. The digital stabilization is divided into three modules, image registration or motion acquisition, motion vector estimation and motion vector compensation. In this project we propose to obtain the image registration using an enhance Block Matching Algorithm, and using a local temporal Gaussian filter as the vector compensation. This matching gives us a good result in terms of the computational speed and the image stabilization